First report of marine Gastrotricha from Chilean beaches - Schmidt-Rhaesa, Andreas; Lee, Matthew; Scherf, Marina; Figueroa, Tania; Sellanes, Javier; Cañete Aguilera, Juan Ivan (My University, 2019)
ABSTRACT A recent study of the meiofauna from several intertidal sites along the coast of Chile yielded several gastrotrich specimens. The number of specimens was too small to assess the ecology of the individual species; however, as there are no published records of Gastrotricha in Chile until recently, it is important to document the presence of this group in order to stimulate further research. We report specimens of the genera Lepidodasys, Cephalodasys, Macrodasys, Tetranchyroderma, Xenotrichula and several morphotypes of Turbanella. Additionally, we provide some initial data on the population density of Lepidodasys sp. at Coihuin (Puerto Montt) and an observation of them feeding on nematodes.
Keywords: gastrotricha; lepidodasyidae; macrodasyidae; turbanellidae; thaumastodermatidae; benthic; biodiversity; chile